THE CLASSICISM OF HUGH TREVOR-ROPER. (26th August 2015) - Malloch, S. J. V.
Abstract : Hugh Trevor-Roper was educated as a classicist until he transferred to history, in which he made his reputation, after two years at Oxford. His schooling engendered in him a classicism that was characterised by a love of classical literature and style, but rested on a repudiation of the philological tradition in classical studies. This reaction helps to explain his change of intellectual career. His classicism, however, endured: it influenced his mature conception of the practice of historical studies, and can be traced throughout his life. This essay explores a neglected aspect of Trevor-Roper's intellectual biography through his 'Apologia transfugae' (1973), which explains his rationale for abandoning classics, and published and unpublished writings attesting to his classicism, especially his first publication 'Homer unmasked!' (1936) and his wartime notebooks.